2019
DOI: 10.12968/live.2019.24.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Changing farmer and veterinarian behaviour around antimicrobial use

Abstract: Slowing the development of antimicrobial resistance (AMR) requires reducing antimicrobial use (AMU), which necessitates altering prescribing practices and reducing use in food-producing species ( O'Neill, 2015 ; World Health Organisation, 2018 ). The literature has suggested for many years that we should try a different approach to changing practices on farm ( Chambers et al, 1985 ) and calls for more farmer-led initiatives compared with traditional, passive knowledge transfer that commonly occurs in the veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Whilst it is important for research to consider the practices and facilities which can promote good calf health-and there has been much research in this area [4,59,60]-the individuals responsible for providing calf care must not be overlooked [45,61,62]. Farmer-led participatory approaches, where farmers are facilitated to learn best practice from peers, can motivate and empower them to make changes and regain control [63,64], suggesting that these approaches could be beneficial in achieving the continuous improvement of rearing practices resulting in better calf health and welfare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst it is important for research to consider the practices and facilities which can promote good calf health-and there has been much research in this area [4,59,60]-the individuals responsible for providing calf care must not be overlooked [45,61,62]. Farmer-led participatory approaches, where farmers are facilitated to learn best practice from peers, can motivate and empower them to make changes and regain control [63,64], suggesting that these approaches could be beneficial in achieving the continuous improvement of rearing practices resulting in better calf health and welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Routine treatment of calf diarrhoea with antibiotics has been shown to have minimal or negative effects and, hence, is not recommended [4] unless calves are systemically ill [18,74]. However, antibiotics were previously recommended as standard treatment and used indiscriminately [75], and challenging these established, habitual practices is difficult [63]. Improving protocols around vaccinations and antibiotic treatments in calves is an essential part of antimicrobial stewardship, but it is necessary to consider farmer opinions and mindset, as well as technical issues [61], and the approach of the veterinarian can influence behaviour change in farmers [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational seminars should be used to identify AMU training needs and raise more awareness about AMR and prudent AMU among beef producers. However, scholars in Europe suggested that providing a sense of ownership of the recommendations for judicious AMU [32] and farmer-led approaches [13] can be useful in causing behavioral change among producers. Exploring appropriate methods for quantifying on-farm AMU in the U.S., may be invaluable since such measures could cause behavioral change towards prudent AMU.…”
Section: Discussionmentioning
confidence: 99%
“…Helke and others [12] suggested that an emphasis on public education, including agricultural education, is critical for facilitating prudent AMU in animal production. Furthermore, a farmer-led approach [13], the whole-of-society approach to antimicrobial effectiveness [7] and One Health approaches to optimization of AMU [14] have been suggested as measures for prolonging the therapeutic life of available antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%